Empathy Huddles: Cultivating a Culture of Empathy. Issue 3 (June 2019) - Turner, Kevin; Locke, Angela; Jones, Tina; Carpenter, Jacque
Abstract : ABSTRACT: Managing complex neurological patients challenges new nurses with minimal experience, which can interfere with their ability to relate empathetically to their patients. This article is the story of how 1 neuroscience unit's experience with Empathy Huddles improved the staff's ability to respond to their patients and families with empathy. The hospital collects quarterly patient satisfaction data using the Hospital Consumer Assessment of Healthcare Provider and Systems. In the third and fourth quarters of 2015, the unit's patient satisfaction scores had declined significantly and remained low, in particular, the score for "how often did nurses listen carefully to you." In February 2016, Empathy Huddles were implemented on the unit. Hospital Consumer Assessment of Healthcare Provider and Systems scores for this question were compared pre and post intervention. The top box response score was 46% preintervention (fourth quarter of 2015). After 2 quarters of Empathy Huddles, the top box score rose to 75% in the third quarter and 82% in the fourth quarter of 2016. The unit has maintained the top box score above 78%. In the fourth quarter of 2017, they achieved a top box score of 91%. Scores greater than 82% were sustained through the third quarter of 2018. Connecting was the overarching theme that emerged from interviews regarding Empathy Huddles. Interviewees described how Empathy Huddles helped them to connect empathetically with their patients, families, and each other. The huddles reminded staff to consider the day from the patients' point of view and be mindful of their experiences.